KAJIAN PSIKOANALISIS JACQUES LACAN DALAM FILM OPERA JAWA (Analisis Fase The Real Tokoh Ludiro) - Zamroni, Muhammad (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2018)
This research aims to: (1) analyzing the psicology of Ludiro in the Opera Java film’s at the process to the Real stage according to the psychoanalytic theory of Jacques Lacan through the film forming alements, especially dialogue and the mise en scene; (2) motivating further research into psychoanalysis in the field of television and film. The subject in this study is the Java Opera film produced in 2006 by the SET Film Workshop and directed by Garin Nugroho. The object studied is Ludiro's character through film-forming elements and the psychoanalysis of Jacques Lacan. This research is a qualitative descriptive research with inductive analysis. Primary data of this research are Garin Nugroho's Java Opera film and the psychoanalytic theory of Jacques Lacan and secondary data in the form of thesis, journals, and books supporting the main theory. Data collection techniques were conducted by non-participant observation and literature study. The data that has been obtained is subsequently reduced and presented in the form of scene screencapture, chunks of dialogue and description to explain the discussion.